THE ROLE OF AMICUS CURIAE IN IMPROVING THE QUALITY OF JUDICIAL DECISIONS IN CRIMINAL CASES IN INDONESIA - Yessika Florencia; Milda Istiqomah; Faizin Sulistio (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The criminal justice system in Indonesia has not explicitly regulated the requirements, procedures for submitting, and the position of amicus curiae in the criminal justice system in Indonesia. There are judges who reject the submission of Amicus curiae because there is no procedural law governing it, judges argue that procedural law in the judicial process is very important in realizing legal certainty in Indonesia. Meanwhile, judges who accept amicus curiae applications use Article 5 paragraph (1) of Law No. 48 of 2009 concerning Judicial Power as the basis for accepting amicus curiae in trials. Progressive judges use Amicus curiae in their consideration of their decisions both from a philosophical, juridical and sociological perspective, where the hope is that the judge's decision will not only provide legal certainty but also truly provide a sense of justice and benefit to the parties. This study aims to determine the role of amicus curiae or friends of the judiciary in improving the quality of judges' decisions in the criminal justice system process in Indonesia. This research uses normative juridical method by using statutory approach and comparative approach. The results showed that the existence of amicus curiae can make a positive contribution to the decision of criminal cases in Indonesia. It is time for a regulation regarding the role and position of amicus curiae in the criminal justice system in Indonesia, so that there is an increase in the quality of decisions by accommodating the values of life and development in society.